Advancing Adult Learning in Eastern Europe and Central Asia - Bodewig, Christian; Hirshleifer, Sarojini (World Bank, Washington, DC, 2017)
This report presents available evidence on adult education and training in Europe and Central Asia (ECA), differentiating two separate types: continuing vocational education and training (CVET) for the employed, sought either by employers or individuals, and retraining and second chance education for the non?employed. This paper presents available evidence on the extent and patterns of lifelong learning in ECA. It argues that advancing adult education and training in ECA is important not only to meet the new skills demands but also to respond to a rapidly worsening demographic outlook across most of the region. While it is not equally important for all ECA countries, adult education and training should be high on the agenda of those ECA economies that are closest to the technological frontier and facing a demographic decline, such as the new European Union (EU) member States and Russia. The paper lays out a framework for government action to advance adult learning in ECA through a mix consisting of policy coordination between government and the enterprise sector, a sound regulatory regime and appropriate financial incentives.